RANCANG BANGUN SISTEM INFORMASI PEMBUATAN TICKET SLM PADA PT. XYZ - Setiawan Setiawan; Teddy Setiady; Mohamad Raya Rabani (POLITEKNIK LP3I JAKARTA, 2025)
This research aims to design and build a Service Level Management (SLM) ticketing system at PT. Bringin Gigantara. This system is developed to improve the efficiency and effectiveness of the company's service management, particularly in handling service tickets. The method used in this research is through direct interviews with relevant parties. The resulting system is expected to facilitate the ticket creation process, thereby improving the quality of service to customers. The research results indicate that this system can reduce response times and enhance user satisfaction through the features provided. In conclusion, the designed SLM ticketing system can be effectively implemented and has a positive impact on the operations of PT. Bringin Gigantara.